CONCEPTUALIZATION OF ALLIANCES IN INTERNATIONAL RELATIONS THEORY - Ковальова, О. І. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2019)
Ukraine’s decision to drop non-aligned status was done as the result of a growing understanding of an urgent need to find more effective means to protect the state from external aggression. One of the main means is integration into powerful intergovernmental institutions, primarily, to European and Euro-Atlantic ones. Thus, acquiring membership in the European Union and the North Atlantic Treaty Organization (NATO) is now among the priorities of Ukraine’s foreign policy. In the process of growing global interdependence, alliances gradually become the main form of international cooperation. At the same time, they are increasingly associated with the emergence and spread of wars and conflicts, as well as their prevention. Under the difficult conditions of international interaction, numerous threats to the existence of state, the implementation of state’s foresightful foreign policy depends on the adequacy of understanding of the nature of cooperation and conflict in relations between states by state’s leadership. Therefore, it is vital to expand and deepen the knowledge about the peculiarities of the formation and functioning of alliances, and the behavior of their participants while contacting each other. The concept of alliances lies at the core of the theory of international relations, since alliances can be considered as a means of implementing the foreign policy of the state, and at the same time as vivid indicators for the implementation of mutual obligations by states. The article deals with the key theoretical contributions on conceptualization of the international alliances as one of the main forms of intergovernmental cooperation. The author provides a general overview of academic papers on alliance theory and uncover the main peculiarities of the periods of research on alliance in political science during and after the Cold War. The article discusses main approaches of the international relations theory to the definition of alliances, as well as the prevailing typologies of alliances.